Factors Influencing Dental Care Behavior among Denture Wearers in Bueng Samakkhi District, Kamphaengphet Province - Pradubpong, Suthisa; Kitreerawutiwong, Nithra (NU Journal of Nursing and Health Sciences, 2024)
The purpose of this cross-sectional study was to investigate the oral health care behavior of denture wearers in Bueng Samakkhi District, Kamphaeng Phet Province, Thailand and to identify demographic factors, predisposing factors, enabling factors and reinforcing factors that affect this behavior. The sample consisted of 226 participants, who were recruited through stratified random sampling. Data were collected by a questionnaire based on the PRECEDE model. The questionnaire was confirmed its validity and reliability. The data were analyzed by descriptive and stepwise multiple regression analysis.The result showed that the oral healthcare behavior among the participants was at a good level of 96.0 % ( X-= 37.34, S.D. = 3.59). Multiple regression analysis indicated that having dental care products and denture cleansing materials (β = 0.252), having support from family members and their close surroundings (β = 0.246), having access to dental care facilities (β = 0.191), having access to dental care products and denture cleansing materials (β = 0.179) and having an attitude towards denture care (β = 0.162) all affected the oral health care behavior of the participants by 41.0% (R2Adj = 0.410, F = 30.038, p-value < .001). Additionally, the results of the study suggest that dental health personnel should be available to provide supporting information to establish a positive attitude and to provide access to dental care products and denture cleansing materials.